Education Of Covid-19 Prevention And Providing Of Handsanitizer In Pressing The Spread Of Corona Virus Infection In Cempedak Lobang Village, Sei Rampah Sub-District, Serdang Bedagai District - Bayu Eko Prasetyo; De Lux Putra, Effendy; Yuliasmi, Sri; Wahyuni, Henny Sri (Talenta Publisher, 2020)
Coronavirus disease (Covid-19) was declared a pandemic (a disease whose spread has spread throughout the world) by WHO on March 9, 2020. This disease can be transmitted to everyone regardless of age and has a very detrimental impact both in the health and economic fields. Cempedak Lobang Village is one of the villages in Serdang Bedagai Regency which was affected by the Covid-19 pandemic. One of the precautions that can be taken to reduce the spread of Covid-19 is the application of physical distancing and maintaining hand hygiene through the use of a hand sanitizer. However, the availability of hand sanitizers has become scarce and very expensive so that it is difficult for the public to reach. In addition, there is a lack of compliance and public awareness of the importance of implementing physical distancing, using masks and maintaining personal hygiene, so it is feared that the spread of the virus will become more widespread. This community service is beneficial in providing one solution and alternative to the community of this village in solving health problems that are currently endemic. The team will disseminate and educate on how to prevent Covid-19 infection. Hand sanitizers provided with formulas according to WHO standards and prepared by the community services team as well as educating on how to use and manufacture them so that they can stimulate the community to make their hand sanitizers.